Aspergillus niger associated calcium oxalate otolith in the external auditory canal: an uncommon clinical presentation - Rao, G. V. S.; Yannamreddy, Lavanya Reddy; Rao, G. V. K. Chaitanya; Cuddapah, Shree Rao (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Otolith formation in the external auditory canal (EAC) can result from fungal colonization, particularly by Aspergillus niger, which secretes oxalic acid leading to calcium oxalate crystal deposition. While this mechanism is recognized in other anatomical sites, its clinical presentation in the EAC requires careful diagnostic consideration. This report describes a unique case of unilateral EAC calcium oxalate stone associated with A. niger, occurring alongside contralateral keratosis obturans. A 40-year-old immunocompetent male presented with bilateral ear discharge, hearing loss, and canal fullness. Otoscopy revealed hard masses in both EACs. The right-sided mass was removed under microscopy; the left required surgical excision via a postauricular approach. Specimens underwent histopathological examination and microbial cultures. Histology confirmed keratosis obturans on the right and calcium oxalate deposits on the left. Fungal culture from the left ear identified A. niger. The patient was treated with oral antibiotics and topical clotrimazole. Follow-up over six months showed complete symptom resolution with no recurrence. Post-treatment audiometry confirmed normal hearing thresholds. This case highlights the need for high clinical suspicion of fungal-induced otoliths in patients with chronic EAC obstruction. Bilateral pathology may have differing etiologies, warranting independent evaluation. Targeted surgical removal and antifungal therapy based on histopathology and culture findings can ensure complete recovery and prevent recurrence.